2014
DOI: 10.14814/phy2.12002
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial monolayer culture system for real-time single-cell analyses

Abstract: Many epithelial cells form polarized monolayers under in vivo and in vitro conditions. Typically, epithelial cells are cultured for differentiation on insert systems where cells are plated on a porous filter membrane. Although the cultured monolayers have been a standard system to study epithelial physiology, there are some limits: The epithelial cells growing inside the commercial inserts are not optimal to visualize directly through lenses on inverted microscopes. The cell images are optically distorted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…These iPSC‐RPE had not been identified previously as outliers by structural analysis or gene expression suggesting that evaluation of cellular function is a potential tool for discerning the quality of iPSC‐RPE. The intactness of the epithelial sheet and the electrical activity of the RPE monolayer are essential for its function; thus, iPSC‐RPE are more fully characterized by assessing the responses of confluent monolayers rather than individual cells [49]. Therefore, we expanded our functional analysis of the intact monolayer to several components of the ATP‐mediated purinergic signaling pathway, critical elements in controlling the chemical composition and volume of the SRS [19, 22, 23, 50, 51].…”
Section: Resultsmentioning
confidence: 99%
“…These iPSC‐RPE had not been identified previously as outliers by structural analysis or gene expression suggesting that evaluation of cellular function is a potential tool for discerning the quality of iPSC‐RPE. The intactness of the epithelial sheet and the electrical activity of the RPE monolayer are essential for its function; thus, iPSC‐RPE are more fully characterized by assessing the responses of confluent monolayers rather than individual cells [49]. Therefore, we expanded our functional analysis of the intact monolayer to several components of the ATP‐mediated purinergic signaling pathway, critical elements in controlling the chemical composition and volume of the SRS [19, 22, 23, 50, 51].…”
Section: Resultsmentioning
confidence: 99%
“…The main relevant studies are summarized in Table 1 , Table 2 , Table 3 and Table 4 . In vitro studies have shown that ASL pH is decreased in the context of CFTR mutations, as compared to epithelia carrying WT CFTR [ 8 , 22 , 42 , 43 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. The majority of studies focused on the most frequent CFTR mutation, p. Phe508delCFTR (F508del).…”
Section: Asl Ph In Physiology and Diseasementioning
confidence: 99%